Constitutional patriotism - Müller, Jan-Werner, 1970- (Princeton University Press, 2007)
Constitutional Patriotism offers a new theory of citizenship and civic allegiance for today's culturally diverse liberal democracies. Rejecting conventional accounts of liberal nationalism and cosmopolitanism, Jan-Werner Muller argues for a form of political belonging centered on universalist norms, adapted for specific constitutional cultures. At the same time, he presents a novel approach to thinking about political belonging and the preconditions of democratic legitimacy beyond the nation-state. The book takes the development of the European Union as a case study, but its lessons apply also.